Three Negro spirituals for two pianos - Price, Florence 1887-1953 (Clarnan Editions, 2017)
These pieces are challenging arrangements of well-known spirituals. Based on the composer's manuscripts
With preface, editorial notes, and texts of the spirituals in English
Keywords: Spirituals (Songs) / Instrumental settings / Scores; Piano music (Pianos (2)) / Scores; Spirituals (Songs); Arrangements (Music); Chamber music; Scores